Perception About Hand Hygiene To Prevent Covid-19 Transmission - An Adolescence Survey - Fitrianola Rezkiki; Rahmiwati Rahmiwati; Nelfika Oktia Sari (Journal of Nursing Care, 2021)
Mortality rates for Covid-19 in Indonesia are about 8.9 %, which is the rate that was the highest in South-East Asia. Research at Rutgers University, New Jersey, of 48 children and adolescents, more than 80 percent of patients had severe conditions. More than 20 percent of patients had organ failure, between one or two organs at once, due to Covid-19 infection. More than 40 percent of patients need a breathing apparatus. One of the efforts to prevent the spreading of Covid-19 is doing hand hygiene following protocol Covid-19. Research objectives are to find an adolescent perception to hand hygiene as an effort to prevent the spread of Covid-19. The type of research was descriptive-analytic. Populations were adolescence over 12 to 18 years old. By using simple random sampling, the samples were found with 82 respondents. The data were collected by questionnaire about the perception of doing hand hygiene to prevent the spreading of Covid-19. The data analysis used is descriptive of the frequency and percentage. The research results obtained 63.41 % of adolescents have negative perceptions, and 36.58 % of adolescents with a positive perception. The lowest perception (46.04 %) is on the item about the need to wash their hands before and after doing an activity. It is hoped that health workers can make an approach through health education and socialization of hand hygiene to adolescents to prevent the spread of Covid-19. And It better in the future can assess all adolescents with qualitative method or mixed with more participants included.Keywords: Covid-19, Hand Hygiene, Perception